HRCT/CT and Associated Spirometric Effects of Low Libby Amphibole Asbestos Exposure. Issue 1 (January 2015) - Lockey, James E.; Dunning, Kari; Hilbert, Timothy J.; Borton, Eric; Levin, Linda; Rice, Carol H.; McKay, Roy T.; Shipley, Ralph; Meyer, Cristopher A.; Perme, Charles; LeMasters, Grace K.
<x xml:space="preserve">Abstract</x> Objective: Evaluate the relationship between cumulative fiber exposure and high-resolution or conventional chest computed tomography (HRCT/CT) changes and spirometry of workers with Libby amphibole asbestos exposure. Methods: Of the original 1980 cohort (n = 513), 431 were living and asked to participate. Images were evaluated for localized pleural thickening (LPT), diffuse pleural thickening (DPT), and parenchymal changes. Results: A total of 306 participants provided either HRCT/CT scans (n = 191) or chest radiographs (n = 115). Of the 191 with HRCT/CT, 52.9% had pleural changes and 13.1% had parenchymal changes. Those with LPT only, LPT and/or DPT, or DPT and/or parenchymal changes had mean 6.1, 8.0, and 18.0 loss in percent predicted forced vital capacity, respectively. Conclusions: Exposure to vermiculite containing amphibole fibers is associated with pleural and parenchymal HRCT/CT changes at low cumulative fiber exposure; these changes are associated with spirometric decrements.